2016
DOI: 10.14740/jocmr2576w
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiInfection and Mixed Anxiety and Depressive Disorder: A Case-Control Seroprevalence Study in Durango, Mexico

Abstract: BackgroundThe parasite Toxoplasma gondii (T. gondii) may invade the brain and might induce behavioral changes. We sought to determine the association of T. gondii infection and mixed anxiety and depressive disorder.MethodsThrough an age- and gender-matched case-control seroprevalence study, we examined 65 patients suffering from mixed anxiety and depressive disorder (WHO ICD-10 code: F41.2) attending in a public hospital of mental health and 260 control subjects without this disorder from the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
(27 reference statements)
1
37
0
Order By: Relevance
“…Psychiatric conditions which have been associated either with increased prevalence of Toxoplasma infection or increased levels of antibodies include bipolar disorder (Pearce et al, 2012), general anxiety disorder (Markovitz et al, 2015), mixed anxiety and depressive disorder (Alvarado-Esquivel et al, 2016), aggressive behavior (Cook et al, 2015), and acute convulsive epilepsy (Ae-Ngibise et al, 2015). Exposure to Toxoplasma has also been associated with increased rates of suicidality as measured by the number of actual suicide attempts (Alvarado-Esquivel et al, 2013) or episodes of self-directed violence (Zhang et al, 2012).…”
Section: Toxoplasma Exposure and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Psychiatric conditions which have been associated either with increased prevalence of Toxoplasma infection or increased levels of antibodies include bipolar disorder (Pearce et al, 2012), general anxiety disorder (Markovitz et al, 2015), mixed anxiety and depressive disorder (Alvarado-Esquivel et al, 2016), aggressive behavior (Cook et al, 2015), and acute convulsive epilepsy (Ae-Ngibise et al, 2015). Exposure to Toxoplasma has also been associated with increased rates of suicidality as measured by the number of actual suicide attempts (Alvarado-Esquivel et al, 2013) or episodes of self-directed violence (Zhang et al, 2012).…”
Section: Toxoplasma Exposure and Neuropsychiatric Disordersmentioning
confidence: 99%
“…A recent meta-analysis investigated its association with schizophrenia, bipolar disorder, major depressive disorder (MDD) and addiction (mainly opioid dependence), and found significant association with schizophrenia, bipolar disorder and addiction but not with MDD (Sutterland et al, 2015). In addition, previous reports have associated T. gondii seropositivity with depressive and anxiety symptoms (Groër et al, 2011; Duffy et al, 2015), generalized anxiety disorder (GAD) (Markovitz et al, 2015), obsessive-compulsive disorder (OCD) (Miman et al, 2010), suicidality (Zhang et al, 2012), mixed anxiety and depressive disorder (Alvarado-Esquivel et al, 2016) and aggression and impulsivity (Cook et al 2015). However, negative findings have also been published (Gale et al 2014, Sudgen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, Dalimi and Abdoli 15) and Fekadu et al 16) suggested that latent T. gondii infection is associated with depression. Although Coccaro et al 10) reported no significant difference in depressive symptoms between the seropositive and seronegative groups, a case-control study performed by Alvarado-Esquivel et al 17) reported a higher seroprevalence in depressive patients. Our result also supports the relationship between depression and T. gondii infection.…”
Section: Discussionmentioning
confidence: 93%
“…Alvarado-Esquivel et al 17) also reported about the association between T. gondii infection and mixed anxiety and depressive disorder. Markovitz et al 19) reported that the T. gondii seropositive group has a greater risk of generalized anxiety disorder.…”
Section: Discussionmentioning
confidence: 98%